The Rotor-Stator Study of E-Core Hybrid Flux Switching Motor - Abd Rani, J.; Sulaiman, E.; Ahmad, M.Z; Amin, F. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper explores the combination of stator and rotor of a hybrid flux switching motor (HFSM) through a rotorstator study on E-core stator type of HFSM. The plausible combination of rotor and stator are analysed through open circuit condition to verify the principles of HFSM on the proposed structures and closed-circuit condition to examine the capabilities of the verified structures. The structure producing the highest torque is undergone structural optimisation to refine the performance.